Ciulei. A Director’s Point of View: Book review: Eugen Gyemant, “Universul regizoral Liviu Ciulei/ Liviu Ciulei’s Stage-directing Universe” (București, Editura Liternet, 2020) - BAN, Cristian (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Considering the small number of Romanian books written about theater directors, I think Eugen Gyemant’s volume about Liviu Ciulei’s work as a director but also as a stage designer is one of the most important and surprising books published last year. It has the quality of using a smart structure in which the innovations in the field of directing and stage design of Liviu Ciulei are being followed and analyzed in a way that, as the author states in the introduction of the book, tries to capture more than a documentary and theoretical approach of his work, and more than a research from the director’s point of view. The author, who is also a theater director, is using reviews, essays and other theoretical studies about Ciulei’s work, and with all this material he is recreating the journey back to the performances: he analyses the solutions that Ciulei found and the decisions that he took as a director, making him one of iconic theater artists from the XXth Century.